The Effect of Hadang-Gobak Sodor Training on Self-Confidence Among School-Age Athletes - Yudi Dwi Saputra; Andun Sudijandoko; Made Pramono; Awang Firmansyah; Panji Bana (General Multidisciplinary Research Journal, 2026)
Introduction: This study aimed to examine the effect of Hadang-Gobak Sodor training on self-confidence among school-age athletes. Research investigating Hadang-Gobak Sodor as a culturally based training approach to enhance self-confidence in school-age athletes remains limited. Methods: This study employed a quantitative quasi-experimental method using a pretest-posttest control group design. The design was used to compare changes in self-confidence between an experimental group that received Hadang-Gobak Sodor training and a control group that participated in regular training. Data were analyzed using tests of normality, homogeneity, and inferential statistical analyses to evaluate changes within and between groups. Results: The findings showed that both groups had comparable levels of self-confidence before the intervention. Following the training, the experimental group demonstrated a greater improvement in self-confidence than the control group. Statistical analysis confirmed that the increase in self-confidence among participants who received Hadang-Gobak Sodor training was significant. Conclusion and Suggestion: The findings indicate that Hadang-Gobak Sodor can serve as a culturally based training alternative to support the psychological development of school-age athletes, particularly in enhancing self-confidence. Future studies are recommended to investigate its long-term effects and examine its effectiveness across different age groups, sports disciplines, and cultural settings.